Student Smoking Behaviour and Cigarette Advertisements Around School and Home: A study in Tebing Tinggi City - Abdi Mubarak Syam; Muhammad Zali; Putra Apriadi Siregar; Apriliani Apriliani; Sarah Fadhila Siregar; Desty Adinda; Abdillah Ahsan; Nadira Amalia; Diva Nada Rizki Nuzlan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Backgrounds: Indonesia is the second-largest cigarette market in the world, with an increased smoking rate among young people aged 10-18 years. The latest data show that smoking is increasingly common in youth. Tobacco control will reduce public demand for tobacco products, especially if the supply of tobacco can be limited. Methods: This study, conducted in Tebing Tinggi City, North Sumatra Province, aimed to collect data on the density of cigarette sellers around schools and their impact on students' smoking behavior. The research involved 1914 students from 10 schools, examining factors such as smoking laws, age at first smoking, daily cigarette consumption, location, and advertisements. The study used a cross-sectional design, GPS coordinates, QGIS 3.0 analysis, and in-depth interviews with a Tebing Tinggi City Health Office representative. The findings will be analyzed using the JASP computer program. Results: The study shows that 8.2% of adolescents in Tebing Tinggi City have never smoked, with mixed views on the smoking law. The majority do not smoke, with varying smoking rates and exposure to cigarette advertisements. The study also found a high density of cigarette sellers in junior and senior high schools, indicating a lack of awareness about smoking. Conclusions: Most adolescents in Kota Tebing Tinggi do not smoke, with mixed views on the smoking law. They are exposed to cigarette advertisements in school and home environments, with vendors providing easy access. Increased awareness and effective law enforcement are needed to control cigarette advertising and sales.